Penegakan Hukum Administrasi Dalam Pelayanan Publik Di Desa Silirejo Kecamatan Tirto Kabupaten Pekalongan - Muhammad Zaenun; Abdul Hamid (Manabia: Journal of Constitutional Law, 2022)
Public service is defined as the provision of services or serve the needs of a person, community, or organization that have an interest in the organization according to the procedures and rules subject matter that is determined and aimed at providing satisfaction to the service recipient. Public service is carried out responsibly and in accordance with applicable laws and regulations. Accountability and the value of accountability for the services provided can be create public trust in the service. Trust community is the basis for realizing the creation of good governance or good governance. The problem here is whether public services in Silirejo Village, Tirto District, Pekalongan Regency are in accordance with applicable regulations and the principles of good governance. The formulation of the problem (1) Why is the rule of law in service law not appropriate? (2) How should service administration be public based on good governance? From the results of the discussion, public services in Silirejo Village, Tirto District, Pekalongan Regency are not in accordance with applicable law because administrative law enforcement factors have not been fulfilled. This has an impact on not fulfilling the principles of good governance